Solute Incorporation at Oxide–Oxide Interfaces Explains How Ternary Mixed‐Metal Oxide Nanocrystals Support Element‐Specific Anisotropic Growth. (20th January 2020) - Gliech, Manuel; Görlin, Mikaela; Gocyla, Martin; Klingenhof, Malte; Bergmann, Arno; Selve, Sören; Spöri, Camillo; Heggen, Marc; Dunin‐Borkowski, Rafal E.; Suntivich, Jin; Strasser, Peter
Abstract: Fundamental understanding of anisotropic growth in oxide nanocrystals is crucial to establish new synthesis strategies and to tailor the nanoscale electronic, magnetic, optical, and electrocatalytic properties of these particles. While several growth investigations of metal alloy nanoparticles have been reported, mechanistic studies on the growth of ternary oxide materials are still missing. This work constitutes the first study on the evolution of anisotropic growth of manganese–cobalt oxide nanoparticles by monitoring the elemental distribution and morphology during the particle evolution via scanning transmission electron microscopy–X‐ray spectroscopy. A new growth mechanism based on a "solution‐solid‐solid" pathway for mixed manganese cobalt oxides is revealed. In this mechanism, the MnO seed formation occurs in the first step, followed by the surface Co enrichment, which catalyzes the growth along the <100> directions in all the subsequent growth stages, creating rod, cross‐, and T‐shaped mixed metal oxides, which preferentially expose 100 facets. It is shown that the interrelation of both Mn and Co ions initializes the anisotropic growth and presents the range of validity of the proposed mechanism as well as the shape‐determining effect based on the metal‐to‐metal ratio. Abstract : An anisotropic growth mechanism for manganese–cobalt oxide is established by monitoring the morphological and intraparticle composition. Mn‐rich cuboctahedrally shaped nanocrystals evolve, followed by preferred deposition of Co‐rich domains on the surface. Particle growth along <100> directions is preferred, while the Co‐rich domains act as growth fronts, resulting in multipods with a Mn‐rich core, Co‐rich tips, and a well intermixed interjacent section.